Collision of Media Positions on Assisted Reproductive Technologies. Issue 2 (4th March 2018) - Emelyanova, T.P.; Vopilova, I.E.
Abstract : An analysis of the discourse on assisted reproductive technologies (ART) indicates the predominance of conservative representations of the family. The appearance of new technologies does not change the image of a "normal" family, because concepts connected with surrogate mothers and egg donors are minimally present in the discourse. In this case, there are contradictory points of view in interpretations of the moral permissibility of assisted reproductive technologies from the perspective of demography, sociology, Orthodoxy, and medicine.